Towards smart computing system to determine the appropriate college major suitable with the student’s capabilities - Abou-Alwan, Saad Mamoun AbdelRahman (Journal of engineering sciences and information technology, 2022)
The purpose of this study is to make a conceptual proposal for a smart computer system that would be able to make proposals for several college majors suitable with the student’s abilities by using Machine learning techniques, which is one of the algorithms of artificial intelligence. This system based on multiple inputs, most notably (student's behavior, grades or assessments in all school subjects in (pre- school primary, intermediate and secondary levels)) and then by manipulating these inputs, with other general inputs that are specific to the requirements of all college majors. Now output is made of several college majors that are appropriate to students' abilities using modern methods that are consistent with the smart devices to which they are accustomed.
Keywords: College majors; relevant major; Machine learning